Over-expression of extracellular superoxide dismutase in mouse synovial tissue attenuates the inflammatory arthritis - Yu, Dong Hoon (Korean Society for Biochemistry and Molecular Biology, 2012)
Oxidative stress such as reactive oxygen species (ROS) within the inflamed joint have been indicated as being involved as inflammatory mediators in the induction of arthritis. Correlations between extracellular-superoxide dismutase (EC-SOD) and inflammatory arthritis have been shown in several animal models of RA. However, there is a question whether the over-expression of EC-SOD on arthritic joint also could suppress the progression of disease or not. In the present study, the effect on the synovial tissue of experimental arthritis was investigated using EC-SOD over-expressing transgenic mice. The over-expression of EC-SOD in joint tissue was confirmed by RT-PCR and immunohistochemistry. The degree of the inflammation in EC-SOD transgenic mice was suppressed in the collagen-induced arthritis model. In a cytokine assay, the production of pro-inflammatory cytokines such as, IL-1β, TNFα, and matrix metalloproteinases (MMPs) was decreased in fibroblast-like synoviocyte (FLS) but not in peripheral blood. Histological examination also showed repressed cartilage destruction and bone in EC-SOD transgenic mice. In conclusion, these data suggest that the over-expression of EC-SOD in FLS contributes to the activation of FLS and protection from joint destruction by depressing the production of the pro-inflammatory cytokines and MMPs. These results provide EC-SOD transgenic mice with a useful animal model for inflammatory arthritis research.